Adding value to an abstracting and indexing System: the Case of MyAIS, Malaysia - Zainab, A.N. (2012)
There are problems in (a) identifying the entire scholarly journals published in Malaysia, (b) locating and accessing the journals, (c) knowing who has published what and in which journals; (d) assessing the indexation status of the journals; and the citation received and general impact count of the journals. The Soft Systems Methodology (SSM) is used to frame the study, especially in determining the problem situations, extracting the problems and proposing a solution in rich pictures, initiating the prototype, comparing existing process with those of the proposed system and making improvements from feedback. The prototype MyAIS or Malaysian Abstracting and Indexing System is described, especially the features that adds value to the system and motivate journal publishers and authors to contribute to the system in order to increase availability and accessibility.